Discussions with Louis: Across the Frontiers of Translation. Issue 1 (2nd January 2016) - Montefiore, Alan
Abstract : The occasion of this article, an invitation to open the Oxford study day devoted to the memory and work of my late friend Louis Marin, reminded me vividly of the complexities inherent in our attempted discussions across the frontiers of translation not only between our respective languages, but also between the guiding presuppositions of our notably different intellectual cultures. One of our immediate and leading concerns was that of how best to understand the notion (or notions) referred to in English by the term 'neutrality' and in French by that of 'le neutre'. For Louis to speak of 'le neutre' was, quite naturally, to make reference not just to neutrality, but equally to that which in English is characterised as neuter; and given the much closer connections between philosophy – as it existed at that time at any rate – in France and the discourses of psychoanalysis and literature in general, it was not surprising that Louis' approach to this question found expression in ways very different from those which anyone coming from an intellectual and linguistic background such as my own might have been expected to find readily intelligible. In looking back on our discussions of so many years ago, I am led to reflect not only on such problems of conceptual translation, but at the same time on the differences that may be found in what in one context or another may be recognised as counting as rationally compelling argument and on the difficulties in the way of mutual understanding to which both may give rise.